2020
DOI: 10.1021/acs.inorgchem.0c01625
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Linear Triiron(II) Extended Metal Atom Chain Complex with Fe–Fe Bonds

Abstract: Extended metal atom chain (EMAC) complexes of first-row transition metals with metal−metal bonds have the potential to elicit unique magnetic properties and reactivities. Until now, the library of EMAC complexes with late-first-row transition metals was incomplete because of the omission of a triiron species with Fe−Fe bonding. Herein we report the synthesis and preliminary investigation of the first linear, triiron(II) complex containing close Fe−Fe interactions. The complex is supported by three dianionic 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…The efficiency of the function of density functional theory (DFT) and the basis sets are considered to describe the geometries of the symmetric form complexes [Cr n (L) 4 Cl 2 ] ( 1 : n = 3, L = dpa – ; 2 : n = 5, L = tpda 2– ; 3 : n = 7, L = teptra 3– ) in the quintet ground state, suggested by both experimental , and theoretical research. Considering the calculation ability, the molecular geometries of 1 – 3 under zero electric field were fully optimized at the UB3LYP, UBP86, and UPBE0 levels, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of the function of density functional theory (DFT) and the basis sets are considered to describe the geometries of the symmetric form complexes [Cr n (L) 4 Cl 2 ] ( 1 : n = 3, L = dpa – ; 2 : n = 5, L = tpda 2– ; 3 : n = 7, L = teptra 3– ) in the quintet ground state, suggested by both experimental , and theoretical research. Considering the calculation ability, the molecular geometries of 1 – 3 under zero electric field were fully optimized at the UB3LYP, UBP86, and UPBE0 levels, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past two decades, linear multinuclear metal string complexes have been extensively studied due to their attractive properties, such as strong metal–metal interaction, electrical conductivity, and magnetic behavior, and their potential applications as nanoscale molecular metal wires. In recent years, much interest is focused on the study of linear metal string complexes [M n L 4 X 2 ]. Structural characterizations were carried out for this family with the help of X-ray diffraction, which revealed that the metal ions were colinear and wrapped helically by four ligands with all of the pyridine and amido nitrogen atoms coordinated in a syn form …”
Section: Introductionmentioning
confidence: 99%
“…Typical examples are N -heterocyclic carbene donors, directly obtainable by deprotonation of azolium precursors. As stated above, multidentate ligands with solely hard nitrogen or oxygen donors are excluded, such as bis­(amido)­pyridines, amidinates and extended derivatives thereof, or carboxylates; likewise, hybrid N,O ligands, such as amidates, pivalamidates, or pyridonates, are not covered, and there are many recent reviews and accounts available on metal chains ,,,,,, and dinuclear complexes , supported by such hard donor ligands. However, metal chains featuring mixed donor “short-bite” ligands with at least one soft donor, whether overall neutral or anionic, will be covered, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Arrays of closely spaced metal ions lined up into wire-like structures are known as extended metal atom chains (EMACs) 1 and have been the focus of intense investigation over the past two decades. [2][3][4][5][6][7] This linear topology is often assembled using specifically designed organic ligands, like fully deprotonated oligo--pyridylamines in the all-syn conformation, and may lead to the formation of metal-metal bonds. 8,9 The structural resemblance of EMACs to macroscopic wires and the possibility of a strong electronic communication among metal centers have suggested the perspective use of these species as nanoscale wires in molecular electronics.…”
mentioning
confidence: 99%